2013
DOI: 10.1111/apha.12210
|View full text |Cite
|
Sign up to set email alerts
|

Activation of soluble guanylyl cyclase prevents foam cell formation and atherosclerosis

Abstract: Activation of sGC by YC-1 leads to LXRα-dependent upregulation of ABCA1 in macrophages and may confer protection against atherosclerosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
32
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 46 publications
4
32
0
Order By: Relevance
“…Third, a recently published paper suggests that complete knockout of Gucy1a3 in mice may reduce atherosclerotic plaque formation on a proatherogenic background ( Ldlr −/− ) 37 . In contrast to this study, we and others investigated a partial loss of sGC activity and showed experimentally in mice and functionally in human materials that this leads to increased disease risk 10,3840 . Thus, in the total Gucy1a3 knockout model compensatory mechanisms affecting NO/cGMP signaling, including a marked compensatory increase of Gucy1a2 expression in Gucy1a3 −/− VSMC 37 , may not have been adequately addressed.…”
Section: Discussionmentioning
confidence: 66%
“…Third, a recently published paper suggests that complete knockout of Gucy1a3 in mice may reduce atherosclerotic plaque formation on a proatherogenic background ( Ldlr −/− ) 37 . In contrast to this study, we and others investigated a partial loss of sGC activity and showed experimentally in mice and functionally in human materials that this leads to increased disease risk 10,3840 . Thus, in the total Gucy1a3 knockout model compensatory mechanisms affecting NO/cGMP signaling, including a marked compensatory increase of Gucy1a2 expression in Gucy1a3 −/− VSMC 37 , may not have been adequately addressed.…”
Section: Discussionmentioning
confidence: 66%
“…[16][17][18] Increase in ABCA1 expression in macrophages promotes cholesterol efflux and decreases cholesterol accumulation of foam cells, thereby retarding the progression of atherosclerosis. [33][34][35] For instance, overexpression of human ABCA1 in Apoe −/− mice increases cholesterol efflux from macrophages and slows down the progression of atherosclerosis. 36 Our current findings further con- PT activity and is associated with hyperlipidemia and calcification in CAD patients.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, activation of sGC seems to be rather protective as enhancing cGMP formation reduces the expression of adhesion molecules and leukocyte recruitment [2]. It has also been reported that the activation of the sGC prevents formation of foam cells and reduces atherosclerotic lesions in ApoE -/-mice [28]. Sovershaev et al further demonstrated that treatment with BAY 41-2272 and BAY 58-2667 reduces the expression of tissue factor, which is linked to the initiation of coagulation but also both inflammation and atherosclerosis [25].…”
Section: Discussionmentioning
confidence: 99%